Rate and efficiency of organic carbon assimilation by aquacultured juvenile sandfish Holothuria scabra - Wahyudi, A'an Johan; Indriana, Lisa Fajar; Muhammad Firdaus,; Prayitno, Hanif Budi; Meirinawati, Hanny (Universiti Kebangsaan Malaysia, 2022)
Diet assimilation rate is crucial to the growth and survival of Holothuria scabra juveniles during culture. To understand the assimilation rate and efficiency we assess organic carbon assimilation, which is closely related to the growth and source of variations in diet. We conducted a two-factor experiment, i.e., juvenile origin (cultured and wild H. scabra juveniles), and diet treatment (one control with no additional diet, and three additional diets, i.e., rice bran, dried cow manure, and seagrass Enhalus acoroides extract). We monitored the amounts of each diet that the juveniles consumed and the fecal pellets they egested. The diet, sediment, body walls, and organic carbon content of the fecal pellets were measured using an elemental analyzer combined with an isotope ratio mass spectrometer. Exponential growth was seen in the juveniles fed with rice bran, which had a fecal pellet egestion of 0.12–0.21 gC/d. Stable isotope analysis showed that the contribution of the diet proportion to the growth of the sandfish did not exceed 30%. The range of the assimilation rate was 35.3–62.4 gC/d. The average assimilation efficiency of organic carbon was 43.6 ± 27.7% (max 57.9%). Considering the assimilation rate and efficiency, we suggest a feeding interval of once every two days or twice per week at a rate of 3–5% of the total H. scabra biomass for a juvenile culture system.